Limberg Flap Versus Open Procedure in Treatment of Chronic Pilonidal Sinus - Naeem Ghaffar, Nadia Farooq, Muhammad Shahid Hussain, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: The main purpose of the study is to compare the outcomes of Limberg flap and open procedure to treat the chronic pilonidal sinus. Pilonidal sinus is a disorder of the sacrococcygeal region mostly found in younger folk. Its treatment consists of several methods but in this study, we will go through Limberg flap and open procedure to compare the outcomes of both methods. Study design: Comparative study. Material & Methods: This study was conducted from January 2020 to December 2022. 84 patients included 59 males and 25 females having age between 18 to 40 years were part of the study. All the selected patients were diagnosed with chronic pilonidal sinus and recommended for surgery at sugery Unit1 sir ganga ram hospital Lahore, Pakistan. A total of 84 patients were divided into two groups, group1 consists of 42 patients treated for the Limberg flap technique. Group 2 also contains 42 patients treated for an open procedure. The patients who were suffering from the chronic pilonidal sinus were part of the study while patients who had acute inflammation of the sinus, history of previous treatment of pilonidal sinus were omitted from the study. Results: Out of 84 patients 42 were part of group 1 and the remaining 42 were in group 2. In group1, the mean ±SD age of patients was 26 ± 2.00, 30 (71.4%) males and 12 (28.5%) females. While in group2 the mean ±SD age was 25 ± 3.00, 29 (69%) were males and 13 (30.9%) females were part of this group. The measured p-value for both groups was <0.05. General characteristics of patients show that high percentage of males was affected from pilonidal sinus disease. In group1 patients who had a 2 days stay at the hospital, recurrence was reported in 10 (23.8%) patients with P-value >0.05, irregular scar formation was observed in 16 (38%) patients, the pain was reported in 18 (42.8%) patients, and wound healing after 2 weeks was noted in 20 (47%) patients. In group 2, patients had 6 days stay at the hospital, recurrence was reported in 13 (30.9%) patients with value >0.05, irregular scar formation was observed in 26 (61%) patients, the pain was reported in 34 (80%) patients and wound healing after 2 weeks was noted in 12 (28.57%) patients. p-value was measured <0.05 for all the parameters. Conclusion: Eventually, we concluded significant results of the Limberg flap than the open procedure. A high percentage of complications were measured in patients treated with the open procedure in comparison to the Limberg flap.